A experiência do horror: arte, pensamento e política - Araújo, Rafael (2009)
This paper portrays different ways of experiencing horror, from the existing relationship between art and thought, looking for understanding some of the political forces that act over humanity in distinct contexts. We start off by the principle that experience of horror accompanies mankind since the first social forms and, through it, it s possible to look at the human condition and situations generated by the difficult sociability. The analysis of these difficulties involves the recognition of circumstances that act over humanity and set violence situations, impotence and suffering. The experience of horror in face of world s reality starts off by the individual itself attesting the Cartesian rationality consequences, and broadens toward the collective, revealing social and political problems, specially with modernity, when the work world asserts itself to mankind in an absolute way and life becomes something disposable. The pieces of artwork selected to the study express different ways of horror, produced in distinct contexts of oppression and carry on themselves important information about the worldly reality. The analysis of these works allowed new perspectives and established a dialogue with some thinker s ideas. In front of the absurd of the world, in which assignments appear to be tragic by its unachievement, an affirmative thought points to a creative way of existing, which diagnoses, values and potentiate life